Apakah Pengungkapan Wajib dan Manajemen Laba Berperan pada Nilai Perusahaan? - Nurlaila Maysaroh Chairunnisa (Jurnal Riset Akuntansi dan Keuangan, 2022)
This study aims to determine the effect of mandatory disclosure and earnings management on firm value. This study uses panel data regression with the object of research is manufacturing companies. The sampling technique in this study was purposive sampling with the criteria of manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019, publishing complete financial statements for the 2017-2019 period, and having their financial statements audited by an independent auditor. Firm value variable uses price book value, mandatory disclosure variable is proxied by IFRS compliance, presentation and disclosure checklist 2017 issued by Deloitte, and earnings management variable is proxied by real earnings management. The results of this study are mandatory disclosures have no significant effect on firm value and earnings management has a significant negative effect on firm value.